A Rare Case of Light Chain Amyloidosis of the Gastrointestinal Tract. (30th June 2020) - Dvir, Kathrin; Galarza-Fortuna, Gliceida M.; Willet, Anna; Febres-Aldana, Christopher; Cortez, Nathaly; Rapaka, Samuel; Coombs, Andre; Goldberg, Robert; Schwartz, Michael; Ben-David, Kfir
Abstract : A 65-year-old Hispanic female presented with a one-year history of anorexia, nausea, early satiety, epigastric discomfort, and a 20 kg weight loss. Computed tomography (CT) demonstrated heterogeneous liver parenchyma. Upper endoscopy revealed large, fungating, infiltrative mass at the lesser gastric curvature incisura, highly suspicious of gastric tumor; however, initial biopsy of the gastric mass was equivocal and an exploratory laparoscopy was performed. Repeated intraoperative biopsies of the gastric mass and of liver parenchyma demonstrated diffuse hyalinized stroma consistent with amyloid deposition, and a bone marrow biopsy confirmed the diagnosis of primary light chain (AL) amyloidosis.